Formulating an eco-friendly asphalt mix using recycled plastic waste: A sustainable approach - Mohd Saad, Rosidah Binti; Jusoh , Hanison; Ngadiman , Dicky Wiwittan Toto (Jurnal Penyelidikan Sains Sosial, 2025)
This study evaluated the effectiveness of recycled plastic as an additive in asphalt to improve road durability and reduce plastic pollution. The test samples contained a mixture of PET and LDPE plastics at 4%, 5%, and 6%, which were tested using the Marshall Stability Test and Water Absorption Test. The results showed that 6% plastic provided the highest stability (16.3 kN) and the lowest water absorption rate (1.0%), making it more resistant to traffic loads and moisture. This study supports the use of recycled plastic in more sustainable and environmentally friendly road construction, with the potential to reduce reliance on conventional bitumen. The study methodology involves experimental sampling by producing four types of asphalt samples, namely control samples (0% plastic), 4%, 5%, and 6% plastic, which are then tested using water permeation tests and Marshall Stability tests to evaluate their mechanical performance. The population of this study includes construction materials used in road construction, while sample selection is done based on the controlled random sampling method to ensure more valid results. The expected findings show that the use of recycled plastic can increase the resistance of asphalt to mechanical loads and reduce the air permeation rate, thus improving the lifespan of roads. Significantly, this study contributes to increasing the durability of road infrastructure while reducing plastic pollution, changing the green approach that can be applied in the construction industry. In addition, new knowledge highlighted in this study is the optimization of the plastic mixture rate in asphalt to achieve a balance between flexibility, strength, and air resistance, which has not been widely explored in the context of road maintenance in Malaysia.